Cubic spline based particle swarm optimization for microstrip antennas - Moniruzzaman, Md.; Islam, Md. Rafiqul; Kamaruzzaman , Sopian; Saleem , H. Zaidi (INSI Publications, 2011)
This paper presents an optimization technique for microstrip antennas using cubic spline based particle swarm optimization (CSPSO). An application of this algorithm is developed for microstrip antenna optimization. An initial antenna is designed by searching an acceptable solution from collective range of antenna parameters. The data for developing the CSPSO program is obtained from simulation software by varying different parameters of the antenna. Using the generated data, the CSPSO program is developed and executed. Thus the optimized antenna is obtained. Finally the performance of the initial antenna is compared with the CSPSO optimized antenna. The result yields that CSPSO shows remarkable improvement over bandwidth. For the probe fed microstrip antenna, the bandwidth is increased by 19% compared to the initial antenna.